Roots Tourism History and Experiences in France - Philippe, Clairay (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2023)
Roots tourism is developing in Italy, both in the field, through the intermediary of companies that host and supervise it, and in terms of training, with the creation of a master’s degree in roots tourism at the University of Calabria at the end of 2020, and finally thanks to the political support and encouragement of the Italian state. What is the situation in France? This paper will try to compare our two countries in terms of the organization of tourism and its development structures. Roots tourism is a relatively recent concept which, in France, seems to be in its infancy, while the pool of tourists concerned is very large. To understand this apparent contradiction, we will look at a form of tourism that in some ways masks the real weight of ’family’ roots tourism in France: this is remembrance tourism, which is omnipresent, developed and well-regulated in France, particularly around the battlefields of the two world wars. We will then show that two types of roots tourism can be developed in France: an endogenous type, perhaps the most obvious (linked to the rural exodus of the 19th century and the rediscovery, today, of the countryside for a return effect) and an exogenous type linked to the longer history of France and its links with Quebec and its former African colonies. In contrast, genealogical tourism and roots tourism seem to be still underdeveloped, whereas their supervision (private or public) could generate a new tourism economy that is still in its infancy. According to some specialists, roots tourism is said to be much more inclined to discover ’authentic’ territories and their cultures, and would provide an alternative to mass tourism, to ’classic’ tourism, which is now criticized as depredatory and polluting. The conclusion of this paper will show how the current post-Covid-19. context favors this more personalized and perhaps more intimate type of travel. Thus, there is no doubt that roots tourism is becoming a promising part of the tourism economy.